Cystic fibrosis clinical characteristics associated with dornase alfa treatment regimen change. Issue 1 (24th October 2017) - VanDevanter, Donald R.; Craib, Marcia L.; Pasta, David J.; Millar, Stefanie J.; Morgan, Wayne J.; Konstan, Michael W.; ,
Abstract: Background: When the chronic respiratory therapy dornase alfa was made commercially available for cystic fibrosis (CF) more than 20 years ago, two regimens were approved: 2.5 mg inhaled once daily (QD) or twice daily (BID). In the intervening years, there has been little guidance as to when to use each regimen. We have studied clinical practice patterns captured in the Epidemiologic Study of CF (ESCF) during the decade following dornase alfa approval (1994‐2005) to better understand clinical characteristics associated with QD versus BID dornase alfa use. Methods We studied the characteristics of ESCF patients who received either dornase alfa regimen for at least 12 months and who were then switched to the alternate regimen for at least 6 months and who had adequate data available around the time of the switch. Average lung function and weight‐for‐age (WFA) z ‐scores, numbers of intravenous (IV) antibiotic‐treated pulmonary exacerbations, and prevalence of signs and symptoms were determined for 6‐month periods capturing the beginning (FIRST) and the end (LAST) of the initial regimen, the 6 months preceding the final 6 months of the initial regimen (PRIOR), and the beginning of the second regimen (POST). Changes in values from FIRST to LAST, PRIOR to LAST, and LAST to POST were studied to better understand clinical scenarios associated with decisions to change regimens. Results: A total of 1342 QD and 574 BID regimens were studied with median durations of 3.19 and 2.09 years, respectively. On average, patients beginning BID regimens had worse lung function and a greater number of pulmonary exacerbations treated with IV antibiotics than those beginning QD regimens. However, by the time of regimen switch, patients switching from QD to BID dornase alfa had experienced substantial deterioration with respect to pulmonary exacerbations and signs and symptoms, whereas patients switching from BID to QD had not. Interestingly, incidence of IV‐treated pulmonary exacerbations and signs and symptom prevalence decreased for both populations after regimen switch. Conclusions: We have studied populations of patients with CF receiving dornase alfa who were switched between regimens to characterize clinical course. Our results suggest that the most common clinical attribute associated with switching from QD to BID dornase alfa was a marked deterioration in stability characterized by increased incidence and frequency of pulmonary exacerbation. For this population, deterioration in lung function did not appear to be a driver for this switch. In contrast, patients receiving BID dornase alfa who were ultimately switched to QD appeared to be clinically stable, on average, suggesting that treatment burden and cost may have been drivers of the decision to switch regimens.